Behind caring: the contribution of feminist pedagogy in preparing women for Christian ministry in South Africa - Ryan, Mary Bernadette (2009)
This research investigates the complex nature of caring in relation to women in ministry, in particular when women's roles as carers are subsumed into a patriarchal agenda in the church, with negative effects for women. The thesis explores this as an ethical problem that confronts women, but also those who are training women for the ministry. It proposes that feminist pedagogy provides important insights, tools and analyses which, when incorporated into women's formation, can help to counter these negative tendencies and the way women have internalised them. The findings of the research suggest that a critical ethic of care, which incorporates biblical principles of compassion and justice, is central to the liberating praxis of women in ministry. This has two important consequences: Firstly, it has implications for the women and how they assert themselves as moral agents of critical caring in their ministry. It suggests that in addition to the traditional caring work that women do, women also care when they seek justice by challenging the status quo understandings and practices of caring. In addition, women care when they look after themselves: when they seek healing, when they scrutinise their roles and responsibilities, and in some cases, make decisions not to care. Secondly, a critical ethic of care has implications for theological education at the epistemological, the pedagogical and the practical levels. The findings from the empirical research, based on two case studies of a Women's Studies course, have helped to identify the kinds of changes that are necessary. These include revisioning the theological content that is taught, as well as the teaching methodologies. Changes to the institutional culture and the relationships within it are necessary so that the institutions become more welcoming and hospitable to women. This thesis suggests that educators have an ethical responsibility to prepare women with the necessary knowledge and skills for the difficult, and often uncaring, terrain of their local churches. It concludes by challenging women to take responsibility for inserting themselves into local communities of practice, as a vehicle for their ongoing formation and support once they leave the theological institution. === Systematic Theology & Theological Ethics === DTH (THEOLOGICAL ETHICS)